The physical determinants of maximal jumping time of flight in elite trampolining - Dyas, N.; Green, D.; Thomas, K.; Matthew, E.; Howatson, G. (European Journal of Sport Science, 2023)
Time of flight (ToF) is an objective scoring component of elite trampolining, assessed in training by maximal jump tests. The aim of this study was to assess the relationship between physical floor based performance meaures and 20-maximum ToF. Thirty-two elite level gymnasts (13 senior; 19 junior) performed a battery of floor based tests and a 20-maximum jump test. Floor based tests included cycling peak power output, reactive strength index (RSI), unloaded countermovement jumps (CMJ), and loaded CMJ`s to construct a load-velocity profile for prediction of theoretical maximum force (CMJ F0). Very large and large, positive bivariate relationships were observed between CMJ F0 and ToF for the seniors (r = 0.85) and juniors (r = 0.56), respectively. Very large, positive bivariate relationships were observed between CMJ height and total ToF for both seniors (r = 0.74) and juniors (r = 0.77). Step-wise multiple regression analyses revealed CMJ F0 predicted 72% of ToF variability between seniors, and CMJ height (59%), 10 to 5 RSI (13%), and CMJ F0 (10%) predicting 82% of ToF variability between juniors. This suggests CMJ F0, lower limb maximal isometric capabilities, and CMJ height are important floor based predictors of maximal ToF in elite gymnasts.